Earthquakes, Religion, and Transition to Self-Government in Italian Cities - Marianna Belloc; Francesco Drago; Roberto Galbiati (Center for Economic Studies and ifo Institute (CESifo), 2015)
For a panel of 122 cities observed over 300 years in medieval northern-central Italy, we document that the occurrence of an earthquake retarded institutional transition from the feudal regime to the commune (free city state) in cities where the political and the religious leaders were one and the same person, but not in cities where political and religious powers were distinct. This effect holds both for destructive seismic episodes and for events that were felt by the population but did not cause any material damage to persons or objects. These findings are consistent with the idea that earthquakes represented a positive shock to people's religious beliefs and enhanced the relative ability of politicalreligious leaders to restore social order after a crisis with respect to the emerging communal institutions and civic associations. This interpretation is supported by historical evidence.
Keywords: D70; P16; Z12; 330